The acute adrenal stimulation anoxemia variation expressed in circulating eosinophils - Monge M., Carlos (1954)
The problems of living at altitude have raised interest and concern, and induced multiple studies Peruvian and foreign researchers. The desire for understanding has been that the man living there has balanced against environmental physiology rigor as that inhabit the sea level rises to high mountains, thus being subjected to an "anoxic aggression" against having to fight.